2022
DOI: 10.1002/widm.1461
|View full text |Cite
|
Sign up to set email alerts
|

Machine intelligence in dynamical systems: \A state‐of‐art review

Abstract: This article is dedicated to study the impact of machine intelligence (MI) methods viz. various types of Neural models for investigating dynamical systems arising in interdisciplinary areas. Different types of artificial neural network (ANN) methods, viz., recurrent neural network, functional‐link neural network, convolutional neural network, symplectic artificial neural network, genetic algorithm neural network, and so on, are addressed by different researchers to investigate these problems. Although various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The accuracy of the proposed MhWNN-LBFGS algorithm has been shown in the tables and graphs. Different global statistical measures (NSE, MAPE, TIC, and RMSE) are evaluated, for convergence analysis of MhWNN-LBFGS model which is defined as below [30] NSE= ( )…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The accuracy of the proposed MhWNN-LBFGS algorithm has been shown in the tables and graphs. Different global statistical measures (NSE, MAPE, TIC, and RMSE) are evaluated, for convergence analysis of MhWNN-LBFGS model which is defined as below [30] NSE= ( )…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…After that, researchers have extensively investigated DEs including non-linear systems, in the context of ANN. However, researchers have proposed variants of NN for solving DEs with distnict properties such as fractional DEs, fuzzy DEs, stiff DEs, disease models etc [6][7][8]. Many essential works on neural network models in order to solve DEs have been done in past few years [9][10][11][12][13].…”
Section: Related Studiesmentioning
confidence: 99%
“…The uncontroverted gains to health technology should not be patronized by feigned unethical organizations and individuals. A study by [9] indicated that "different types of MI and a variety of artificial neural network (ANN) methods among any related learning algorithm applications can be an incentive to a new area of research involving dynamical systems and will help in developing best performing models". In his study Bhattacharyya et al (2022) brought forward for "consideration a novel approach for covid-19 X-ray CT image categorization with the aim of coming up with an efficient tool based on the conditional generative adversarial network (C-GAN).…”
Section: Opportunity In Healthcarementioning
confidence: 99%